Contribution of Women Through Their Unpaid Work in Urban Punjab. (1st April 2016) - Singla, Sushma; Singla, Anil Kumar
Abstract: The aim of the present study was to estimate the contribution of women towards the nation's economy and social development through their unpaid work. Primary data for the study was collected from 360 working and non-working women of three different income groups that is LIG, MIG and HIG from two major cities of Punjab namely, Patiala and Ludhiana. Results relating to the non-economic contribution of women have shown that most of them under study (351/360) performed daily household chores by themselves, and hence contributed indirectly towards their family income by saving some money. The average number of household chores performed by working (3.27) and non-working (3.36) women showed that working women do not lag far behind the nonworking women, thus, both working and non-working women have almost equal contribution in the exchequer of their families. On an average, a woman saved INR 1, 873 per month by way of doing household chores by herself.